Genomics of Otitis Media (OM): Molecular Genetics Approaches to Characterize Disease Pathophysiology - Giese, Arnaud P. J.; Ali, Saadat; Isaiah, Amal; Aziz, Ishrat; Riazuddin, Saima; Ahmed, Zubair M. (Frontiers in Genetics, 2020)
Otitis media (OM) is an infective and inflammatory disorder known to be a major cause of hearing impairment across all age groups. Both acute and chronic OM result in substantial health care utilization related to antibiotic prescription and surgical procedures necessary for its management. Although several studies provided evidence of genetics playing a significant role in the susceptibility to OM, we had limited knowledge about the genes associated with OM until recently. Here, we have summarized the known genetic factors that confer susceptibility to various forms of OM in mice and humans and their genetic load, along with associated cellular signaling pathways. Spotlighted in this review are Fucosyltransferases (FUTs) enzymes, which have been implicated in the pathogenesis of OM. A comprehensive understanding of the functions of OM-associated genes may provide potential opportunities for its diagnosis and treatment.